(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article is devoted to the study of the main problems that hinder the growth of the potential of the mortgage lending market in Russia. The authors have determined that mortgage lending is one of the most effective tools for solving socio-economic problems of states in modern conditions. The analysis of the state of the mortgage lending market in Russia was carried out, because of which a gradual increase in the number of funds issued by banks for the purchase of real estate by the population and their volumes was recorded. It is revealed that the main problems in the mortgage lending market in Russia are a strong dependence of market dynamics on the level of creditworthiness of the population, an increase in interest rates, weak competition between real estate developers, and an extension of the loan term. It is determined that mortgage lending can become an effective tool for solving socio-economic issues, provided that preferential programs are expanded, as well as maintaining competition in the housing construction industry.